AMgPO4·6H2O (A = Rb, Cs): strong SHG responses originated from orderly PO4 groups. Issue 39 (21st September 2016) - Zhou, Yuqiao; Cao, Liling; Lin, Chensheng; Luo, Min; Yan, Tao; Ye, Ning; Cheng, Wendan
Abstract : Two UV NLO phosphatesAMgPO4 ·6H2 O (A = Rb, Cs) were synthesized by a soft hydrothermal method. Abstract : Two UV NLO phosphates AMgPO4 ·6H2 O (A = Rb, Cs) were synthesized by a soft hydrothermal method. RbMgPO4 ·6H2 O originates from the struvite structure type and crystallizes into the orthorhombic space group Pmn 21 . CsMgPO4 ·6H2 O derives from the nickeline structure type and crystallizes in the polar space group P 63 / mmc . The structure of CsMgPO4 ·6H2 O features two-layer arrangements, while there is only one layer in the struvite RbMgPO4 ·6H2 O. Without the spatial inhibition of corner-shared behaviour, the isolated PO4 groups in CsMgPO4 ·6H2 O align in parallel to make maximum contribution to achieving high-performance nonlinear properties. The d eff coefficient for CsMgPO4 ·6H2 O is 0.53 pm V −1, which is one of the strongest SHG responses among reported UV NLO phosphates. In addition, CsMgPO4 ·6H2 O shows a wide transparent region ranging from UV to near IR with a UV cutoff edge at approximately 258 nm.